Crystallization and characterization of struvite crystals through gel growth technique - Salsabili, Ahmad (2017)
Crystal growth or crystallization is defined as controlled phase or state change to solid state. This state transition might happen from any state of matter, liquid, gas or solid to solid state which are crystals. Crystalline materials produced through chemical reaction in any media can readily be controlled in order to increase the crystal size, yield and change the crystals morphology. However, the gel media is known to be one of the best media for investigating the effects of different operational parameters on crystals size, morphology, yield and purity so far. Magnesium ammonium phosphate hexahydrate (MgNH4PO4.6H2O) which is better known as struvite, is one of the most fascinating inorganic phosphate compounds. There are several reasons associated with the study of struvite crystals. First of all, it is one of most popular scale deposits in wastewater treatment plants. Second of all, struvite is known as one of the major components of urinary calculi. Crystallization and characterization of struvite crystals grown in gel media has been carried out in the current study. Struvite crystals were grown in two different gels of gelatin and silica gel using both single and double diffusion crystallization techniques. The pH ranged from 6 to 9 for silica gel and gelatin. Different gel densities were practiced ranging from 1.04 to 1.08 for silica gel and 1.04 to 1.11 for gelatin. Totally the crystals grown in silica gel had more variety of morphologies and the silica gel itself demonstrated less number of limitations compare to gelatin gel. Crystals with prismatic, pyramidal, dendritic, star shaped and branched star shaped morphologies were grown through this technique mainly in silica gel. The grown crystals in both gel media have been characterized by SEM, EDX and FTIR sets. The SEM test revealed the inner morphology, crystal size and the volume of cracks inside the crystals. EDX test proved the existence of comprising elements, namely phosphorous, oxygen and magnesium. The FTIR test revealed the internal chemical bonds of N-H, O-H, P-O, water of crystallization and metal oxygen bonds. The FTIR results are presented and compare to other studies carried out formerly. The harvested struvite crystals grown within different operational conditions were analyzed by powder X-ray diffraction (XRD) set. The crystal size was calculated based on Scherrer equation which ranged from 27.9124 to 32.5919 nm. It has been found that struvite crystallizes in the orthorhombic (single-phase) Pmn21 space group with unit cell parameters: a = 6.9550 Å, b = 6.1420 Å, c = 11.218 Å and α = β = ϒ = 90°. Totally, the crystals grown in pH of 8 had larger crystal size. This was also approved by the SEM analysis showing less amount of cracks happening at this pH value. Struvite crystal habits were analyzed using optical microscopy. All three crystals diaphaneity, transparent, translucent and opaque were noticed in the crystallization of struvite crystals in silica gel. The crystals formed in the acidic pH values (6, 6.5) demonstrated high transparency while the crystals formed at high alkaline pH values had more translucent and opaque diaphaneity. The high alkaline pH value (9) lead to the formation of Liesegang rings which is described in detail in the context. The solubility of produced crystals were analyzed through solubility test. Proportional portions of the harvested crystals were stirred well for one day at constant rate of 400 RPM and after that dried out in the oven at 35 °C. The solubility results revealed that the minimum solubility happens for the crystals grown in gel with pH of 8 at 392 and 474 mg/l for gel SG of 1.07 and 104 respectively. An optimization study based on Taguchi model of experiment design has been carried out and the results were announced. The effects of different combination of four process parameters of gel density, gel pH, magnesium molarity and ADP molarity on struvite crystal size were studied and the results were reported. The results of the ANOVA analysis revealed that pH was the most influential parameter in sense of producing bigger crystals with contribution percent of over 65% followed by magnesium dosage (25%), ADP molarity (7%) and gel density (1%). The kinetics and growth mechanism of struvite crystallization in gel media has been studied in this thesis. For this purpose, both pseudo first and second-order kinetic models were applied to the experimental data. The tests were carried out on the amount of magnesium concentraton changes over time and rate of struvite crystals formation assuming equamolar reaction (consumption) of 1:1:1 for Mg:NH4:PO4. The magnesium concentration was measured at certain intervals and based on the concentration reduction of magnesium, the kinetic rate constants (K1, K2) and rates of reaction (R) for samples grown in various operational conditions were calculated and reported. Based on the results of the kinetic study the experimental data better fits with second-order kinetic model with minimum and maximum R2 over 97% and 99% compare to first-order kinetic model with minimum and maximum R2 of 89% and 95% respectively. The obtained pseudo first and second-order rate constants can be used to explain the struvite crystallization behavior.